Circulating Endocannabinoids in Canine Multicentric Lymphoma Patients - Hay, Jennifer K.; Hocker, Samuel E.; Monteith, Gabrielle; Woods, J. Paul (Frontiers in Veterinary Science, 2022)
The endocannabinoid system is increasingly being implicated in the pathogenesis and progression of various human cancers. Specifically, increased levels of 2-arachidonoylglycerol (2-AG) and oleoythanolamide (OEA) have been demonstrated in human diffuse large B-cell lymphoma (DLBCL) and chronic lymphocytic leukemia (CLL) patients, respectively. The objectives of this paper were to compare 2-AG, OEA, N-arachidonoylethanolamine (AEA), and palmitoylethanolamide (PEA) levels between dogs with multicentric lymphoma and healthy control dogs. In addition, evaluate 2-AG, OEA, AEA, and PEA levels as biomarkers for progression free interval (PFI) and overall survival time (OST) in the dogs with lymphoma. The study consisted of 26 dogs with multicentric B cell lymphoma, 14 dogs with multicentric T cell lymphoma, and 12 healthy control dogs. Serum 2-AG, OEA, AEA, and PEA levels were measured using liquid chromatography combined with tandem mass spectrometry (LC – MS/MS) in dogs with lymphoma and in healthy dogs. OEA, AEA, and PEA levels were significantly elevated in dogs with lymphoma compared to healthy controls (p < 0.05). Total AG was significantly higher in healthy control dogs (p = 0.049). There was no significant difference between dogs with B cell and T cell lymphoma for any of the measured endocannabinoids. Elevated PEA was significantly associated with decreased PFI (p = 0.04) in dogs with lymphoma with a hazards ratio of 1.816 (95% Confidence Interval (CI): 1.020 –3.232). Overall, dogs with lymphoma have elevated levels of OEA, AEA, and PEA. PEA levels have the potential to be a prognostic biomarker.